GENERAL REGULARITIES ON NPS CONSTRUCTION CONCRETE CORROSION PROCESSES AND THEIR SIMULATION - S. N. Leonovich (Наука и техника)
Civil engineering material science has accumulated a great amount of scientific data on corrosive processes occurring in the NPS concrete structures (including the Bushehr NPS, Islamic Republic of Iran) due to environmental conditions.This practical material creates appropriate prerequisites for generalizations, presentation of results in the form of mathematical models permitting to make calculations on durability of the NPS concrete and reinforced concrete  structures with the required accuracy.